PENGARUH PENGETAHUAN DAN SIKAP TERHADAP KESIAPSIAGAAN MASYARAKAT DALAM MENGHADAPI BENCANA BANJIR DI DESA PERKEBUNAN BUKIT LAWANG KECAMATAN BAHOROK TAHUN 2011 - Mukhtar Effendi Harahap; Muslich Lufti Lufti; Abdul Muthalib (Jurnal Ilmiah Keperawatan IMELDA, 2019)
Flood preparedness will show the existence of attitudes and knowledge in the face of disaster and became an important part, especially in areas frequently hit by floods as the village of Perkebunan Bukit Lawang. flooding potentially occurred in the village of Perkebunan Bukit Lawang as in 2004. This is because the nature of the slope of the Bahorok River basin as well as the many people who cut down trees around the river and a lot of activity in near the river. The purpose of this study to analyze the influence of knowledge and attitudes towards community preparedness in the face of catastrophic flooding in the village of Bukit Lawang district Bahorok Plantation. This type of research is analytical research using explanatory approach. The population in this study were all heads of families in the village of Perkebunan Bukit Lawang in 2011, amounting to 740 people to the sample amounted to 89 people drawn at random proportional sampling. Data obtained through interviews using questionnaires, were analyzed with multiple logistic regression. The results showed that statistically there is the influence of knowledge and attitudes towards community preparedness in the face of catastrophic floods in the village of Perkebunan Bukit Lawang in 2011 Variable attitude householders provide the most impact to the value of β coefficient (21.623). Necessary improvement of environmental health, so people are not too exploit nature for his life and eventually destroying the forest. Moreover, given counseling about preparedness in facing the potential hazards that arise in the area, such as floods. In addition, local governments are also expected to create policies that support the implementation of the conservation of protected forests and the prevention of forest destruction in order to prevent the emergence of flood disaster.